Edge habitat preferences in three titi monkey species in Colombia (Cheracebus lugens, Cheracebus torquatus lucifer and Plecturocebus ornatus) - Defler, Thomas Richard; Carretero-Pinzón, Xiomara (Neotropical Primates, 2018)
The three titi monkeys Cheracebus lugens, Cheracebus torquatus lucifer and Plecturocebus ornatus prefer edge habitat when occurring in extensive forests. We present preliminary data showing that these three species exhibit their highest densities at the edges of forest types. In gallery forests of Vichada department, Cheracebus lugens has densities of 8 groups / km2. We found that the same species had crude densities of 0.68 groups/km2 in Vaupés department, while their densities increase in edge habitats to 17.5 groups/km2. Cheracebus torquatus lucifer in Amazonas department exhibits 0.47 groups/ km2 crude densities, while their highest densities are in edge habitats along the Cotuhé River at 17.5 groups/km2. In a large 1,080 ha forest fragment in Meta department, Plecturocebus ornatus exhibit higher densities (around 15 - 17 individuals /km2) in edge habitats facing savanna, as opposed to their overall crude densities throughout this large forest fragment (1.07 ind/ km2). In the case of these P. ornatus, the edge habitat is floristically more diverse than the forest 600-700 m away from the forest edge. But, in Vaupés, the edge habitats used by C. lugens are less diverse than forest in hilly areas found towards the interior of the forest, where Cheracebus densities are lower. There are no comparative floristic diversity data for the forest inhabited by the C. torquatus lucifer in this study. Edge habitat preference is an ecological advantage for species like P. ornatus when its habitat experiences high rates of loss and fragmentation.